PHOENIX DACTYLIFERA L: A BIBLIOMETRIC STUDY OF THE LITERATURE ON DATE PALM - Anwar, Mumtaz A. (Malaysian Journal of Library and Information Science, 2006)
This study carried out a bibliometric analysis of the literature on Phoenix Dactylifera L (date palm). The purpose was to study the periodic growth of literature, author patterns, topical focus, language dispersal, and geographic origin of literature on dates. All related databases and several online catalogues of libraries were searched to identify a final list of 2,465 citations. This data set was analyzed using various bibliographic characteristics. The volume of literature on date palm started increasing from less than one publication per year before 1970 to 80+ papers annually during the 1990s. Most of this literature comes from Agriculture, Biological Sciences, and Chemistry. A small core of authors contributed about one-third of the citations. Four-fifths of the citations are the result of collaborative work. About two-fifths of the papers are published by only 36 journals. Iraq and Egypt are the leading contributors to this literature. English is the most predominant language. The findings of this study will be of benefit to scholars in several disciplines. By identifying various patterns in the literature, it will create awareness among concerned scholars regarding the core authors, core journals that publish this literature, areas where more research is being conducted, and areas where more research needs to be done. It should also encourage researchers to initiate collaborative and inter-disciplinary research.